Heme Oxygenase-1 in Macrophages Impairs the Perfusion Recovery After Hindlimb Ischemia by Suppressing Autolysosome-Dependent Degradation of NLRP3. Issue 5 (25th March 2021) - Ma, Yuankun; Jia, Liangliang; Wang, Yidong; Ji, Yongli; Chen, Jian; Ma, Hong; Lin, Xiaoping; Zhang, Yuhao; Li, Wudi; Ni, Hui; Xie, Lan; Xie, Yao; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: Macrophage-mediated inflammatory response is closely associated with the neovascularization process following hindlimb ischemia. We previously demonstrated that HO-1 (heme oxygenase-1) in macrophages evoked proinflammatory reactions and tissue damage. Here, we evaluated the role played by macrophage-derived HO-1 and elucidated its underlying molecular mechanisms in perfusion recovery after hindlimb ischemia. Approach and Results: We found significant upregulation of HO-1 in mouse ischemic muscles after hindlimb ischemia surgery and with most of this expression occurring in infiltrated macrophages. Myeloid conditional HO-1-deficient mice exhibited higher perfusion recovery, evidenced by restored blood flow, motor function and attenuated tissue damage as well as increased capillary density in the gastrocnemius muscles after hindlimb ischemia, relative to littermate controls. This protective effect was accompanied by reduced NLRP3 (Nod-like receptor family pyrin domain containing 3) inflammasome activation in the infiltrated macrophages without the alteration of macrophage infiltration and polarization. Moreover, suppressing inflammasome activation with NLRP3 inhibitor MCC950 improved blood flow and capillary density in wild-type mice compared with untreated mice. Mechanistically, suppressing HO-1 abolished TNF (tumor necrosis factor)-α-induced NLRP3 protein rather than mRNA expression in bone marrow–derived macrophages, indicating that HO-1 mediated post-transcriptional regulation of NLRP3. Furthermore, HO-1 inhibition promoted autolysosome-dependent degradation of NLRP3 in bone marrow–derived macrophages. Matrigel tube formation assay revealed that HO-1 deletion abrogated the antiangiogenic effect of inflammasome-activated macrophages. Conclusions: Taken together, these findings indicate that macrophage HO-1 deficiency promotes perfusion recovery after hindlimb ischemia by accelerating autolysosomal degradation of NLRP3. The underlying mechanism of action is a potential target for therapeutic angiogenesis in ischemic diseases.